Relationship between Social Participation, Children’s Support, and Social Frailty with Falls among Older Adults in Colombia - Brigitte Alexi Moncayo-Hernández; Eliana Patricia Dueñas-Suarez; Carlos Alfonso Reyes-Ortiz (Annals of Geriatric Medicine and Research)
Background There is limited research on social factors related to falls among older adults. This study assessed the association between falls during the past year with social participation, children’s support, relationship with children, and social frailty. Methods Participants were 17,687 community-dwelling older adults from the 2015 Survey on Health, Well-being, and Aging (SABE) in Colombia. Covariates included sociodemographic characteristics, environmental barriers, psychotropic intake, vision problems, memory loss, multimorbidity, and fear of falling. Results In multivariate logistic regression analyses, being socially frail (vs. no-frail) was associated with higher odds of falls (odds ratio [OR]=1.20; 95% confidence interval [CI] 1.10–1.32). Participating in groups (OR=1.07; 95% CI 1.03–1.11), helping others (OR=1.04; 95% CI 1.02–1.06), or volunteering (OR=1.09; 95% CI 1.01–1.17) were also associated with higher odds of falls. These findings were partly explained because most group participants reside in cities where they are more exposed to environmental barriers. In contrast, receiving help, affection, and company from children (OR=0.95; 95% CI 0.93–0.97) was associated with lower fall odds than not receiving it. Moreover, having a good relationship with children was associated with lower odds of falls (OR=0.75; 95% CI, 0.66–0.85) compared to an unsatisfactory relationship. Conclusion Support from children and having a good relationship with them were associated with fewer falls; however, social frailty and participation in social groups were associated with more falls.